Taḥlīl Tārīkh Ansyiṭah al-Tarjamah fi Al-Ālam al-Islāmī - Agustang Kallang; Sugirma Sugirma (KURAS Institute, 2023)
In this context, this discussion covers the history of translation in the Islamic world, which can be divided into various periods including the Ancient Greek-Roman period, the era of Martin Luther, ancient times, the early Middle Ages, the dawn of modern civilization, the Western cultural era, the early modern era, the industrial revolution era, the end of the second millennium, and the 21st century. This research is of a descriptive qualitative nature, using a historical analysis approach to understand and examine events, processes, or phenomena in a historical context. It aims to identify, analyze, and comprehend the changes and developments that have occurred in the field of translation over time in the Islamic world. The primary focus is on the Abbasid Dynasty, which ruled in Baghdad, and the significant role of translation in integrating foreign influences, such as Greek, Persian, and Indian, into Islamic intellectual culture. Translation of scientific, philosophical, and literary works from Greek, Persian, and Sanskrit into Arabic marked the initial step in the development of rich Arabic literature, including works by renowned figures like Aristotle and Plato. This period created a thriving center of Arabic literature and demonstrated the crucial role of translation in bringing forth a variety of intellectual insights.